PENERAPAN MODEL PEMBELAJARAN TWO STAY-TWO STRAY PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS X AP 2 SMK PASUNDAN 1 KOTA SERANG - Ade Millatus Sa'adiyah; Diana Sekar Anggraini (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2018)
The research problem of this class action is the low motivation to learn civics class X AP 2 SMK Pasundan ! City ofSerang in the academic year 2017. The purpose of this research is to increase student’ motivation on the subjects ofcivic education. The results of this research can be direct benefit to the school is to improve the quality of civiceducatin, besides that it is also useful for teachers and students. This reseach implemented in three cycles, whereeach cycle includes the activites of planning, action, observation, and reflection. Teh subjects of the research arstudent of class X AP 2 as man as 46 student. The troubleshoothing method used is to apply cooperative learningmodel Two Stay – Two Stray on the subjects of civic education, the instrumens of the research is using observationsheet increase student motivation and field notes, implementation of the research conducted collaboratively wihtteachers as obsever and researchers act ang implementers. The results of this research show in creased studentmotivation. The cycle I with an average of 40, 10 % the cycle II with an avarege 57,82% The cycle III with anavarage of 81,95% There fore this classroom action research is successful so the researchers recommended theimplementation of learning model Two Stay – Two Stray can increase student’s motivation on the subjects of civiceducation.